THE EFFECTS OF THE ANONIMITY ON GROUP SUPPORT SYSTEMS COMMUNICATION. A QUANTITATIVE AND QUALITATIVE STUDY - Martínez Martínez, Isabel Mª (Anales de Psicología / Annals of Psychology, 2001)
The new information and comunication technologies facilitates the interaction between people temporary and functionally separate. The objective of the present paper is to analyze the effects of the anonimity on the group results in when they use computer systems. Through a lab-experimental design that considers two situations, identified and anonymous groups, the results are not shown differences in the quantity of messages emitted in function of the anonimity. An categorial analysis of the content has not shown differences in the quantity of flaming communication between identified groups and anonymous.